Availability and affordability of blood pressure-lowering medicines and the effect on blood pressure control in high-income, middle-income, and low-income countries: an analysis of the PURE study data - Attaei, MW; Khatib, R; McKee, M; Lear, S; Dagenais, G; Igumbor, EU; AlHabib, KF; Kaur, M; Kruger, L; Teo, K; Lanas, F; Yusoff, K; et al. (Elsevier, 2017)
Background Hypertension is considered the most important risk factor for cardiovascular diseases, but its control is poor worldwide. We aimed to assess the availability and affordability of blood pressure-lowering medicines, and the association with use of these medicines and blood pressure control in countries at varying levels of economic development.